EVALUATION OF THE NUTRIENT COMPOSITION OF TAMARIND HUSK FOR ITS UTILITY AS AN ALTERNATIVE LIVESTOCK FEED - J. Subhashini; N. Arulnathan; G. Thirumalaisamy; D. Thirumeignanam (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The study was designed to investigate the tamarind husk as an unconventional feed in livestock ration. Tamarind husk samples were collected and analyzed for its nutrient composition. The average dry matter, crude protein, ether extract, total ash, crude fibre and nitrogen free extract of tamarind husk were found to be 89.36, 5.85,1.29, 2.83, 37.15 and 52.88per cent respectively. The non fibrous carbohydrate content of tamarind husk was 17.64 per cent. The mean NDF and ADF of the tamarind husk were 72.39 and 69.45 per cent respectively. The mean calcium and phosphorus content were 1.01 and 0.16 per cent respectively. The total tannin content in tamarind husk was 12.33 per cent. Based on the analyzed nutrient composition, it could be concluded that tamarind husk can be used as an alternative to conventional feed ingredients for livestock.